D-mannose reduces oxidative stress, inhibits inflammation, and increases treg cell proportions in mice with ulcerative colitis - Lu, Yuqing; Xiong, Yongjian; Zhang, Shuangshuang; Wang, Boya; Feng, Yuntao; Pu, Zhuonan; Wei, Kun; Chen, Jun; Chen, Dapeng; Zhang, Peng (Frontiers in Pharmacology, 2024)
Regulatory T (Treg) cells is required to dampen immune responses against intestinal microbiota, which aid in a healthy body to promise that the resident gut microbiota should not attract the attention of the immune system. Inflammation and inflammatory bowel disease (IBD) can be induced if the immune system fails to ignore the resident gut microbiota and targets them instead. D-mannose, a common monosaccharide in nature, has been shown to ameliorate multiple autoimmune diseases. This study aimed to investigate the therapeutic effect of D-mannose on mice ulcerative colitis (UC) induced by 2,4,6-trinitrobenzene sulfonic acid (TNBS), and elucidate its underlying mechanisms. Our results demonstrated that D-mannose treatment effectively alleviated TNBS-induced UC in mice, as evidenced by the amelioration of UC symptoms. D-mannose treatment significantly reduced inflammation by decreasing the expression of proinflammatory cytokines and inflammation mediators. D-mannose treatment also significantly inhibited oxidative stress, promoted the expression of GSH and SOD, decreased the expression of MDA. Mechanistically, D-mannose upregulated the proportion of both CD4(+) Tregs and CD8(+) Tregs. In summary, our study provides the first evidence of the therapeutic effect of D-mannose on mice with UC, which is likely mediated by upregulating Treg proportions.